The Battle for the White House from Bush to Obama - Bennett, A. author. aut Link
XIV, 236 p. 4 illus.
Keywords: Anthony Bennett guides us through the events of the four elections of the 21st century, showing how this era of partisanship has reshaped not only presidential nominations and elections, but the American presidency and politics itself.